Structural Modeling of Cultural Content to Enhance Awareness of Women's Issues in Iraqi Satellite Channels - Khazaal Hammadi, Sabreen; Korang Beheshti, Siamak; Abd-Alrazaq Mostaf Ghrairi , Adel; Aghajani, Mojtaba (Digital Transformation and Administration Innovation, 2025)
This study was conducted with the aim of designing a structural model for cultural content to enhance public awareness of women's issues through Iraqi satellite television channels. The research is applied in nature and employed a descriptive-survey method with a correlational approach using a causal modeling framework. The statistical population consisted of managers, activists, experts, and researchers in the field of media and women's culture, as well as producers and stakeholders involved in television programming and satellite networks in Iraq during the years 2024–2025. As the total population size was unknown, the sample size was estimated to be 384 individuals using Cochran's formula, and convenience sampling was employed. Data were collected through a questionnaire derived from the analysis of qualitative data. The validity of the questionnaire was confirmed by experts, and its reliability was verified through Cronbach's alpha and composite reliability metrics. Data analysis was performed using SPSS and Smart PLS software. Twelve hypotheses were examined regarding the influence of media governance challenges, the representation of women's identity, and the organization of cultural content production. The results indicated that media governance challenges and media transformations had a positive impact on media policymaking. However, media policies themselves did not significantly influence media capacity-building or the production of cultural content. Instead, existing constraints in content production and the media context had a positive effect on media capacity-building and the organization of cultural content. Furthermore, media capacity-building had a direct effect on the transformation of media policies and on enhancing public awareness regarding women's issues.